CFD simulations to study bed characteristics in gas–solid fluidized beds with binary mixtures of Geldart B particles: II quantitative analysis - Ganguli, Arijit; Bhatt, Viraj (Frontiers in Energy Research, 2023)
In the present work (Part II of the two part work on CFD simulations of binary fluidized beds), quantitative predictions of gas velocity and particle velocity profiles have been presented. It was observed that dynamics of the bed varies for different binary mixtures and is a strong function of superficial velocity and bed height. Mixing and segregation in beds for two different initial bed heights, 6 different binary mixtures and superficial velocities have been identified. Segregation is prominent for binary mixtures with 20 wt.% and 80 wt.% of large particles while mixing is observed in 40 wt.% and 60 wt.% of large particles. Bypassing of gas near the walls is prominently seen for 60 wt.% large particles with gas velocities as high as 5 m/s. Time averaged axial particle volume fractions have been observed to be lower in dilute phase with large undulations in middle whenever the bed is well mixed for central axial profiles. The axial volume fraction profiles also confirm the mixing and segregation for the 40 wt.% and 20 wt.% composition of large particles for the operating conditions considered for the study. Bed height expansion is linear till a certain superficial velocity with increase or decrease depending on superficial velocity or bed height of operation. Further, correlations for minimum fluidization velocity and pressure drops from the literature have been compared with experimental results of the literature considered for this manuscript. The simulated data has been considered for the development of a correlation for minimum fluidization velocity. The predicted results match with a 10-15 % deviation of experimental data.